Implementasi Data Mining Pemilihan Pelanggan Potensial Menggunakan Algoritma K Means - Randi Rian Putra; Cendra Wadisman (INTECOMS: Journal of Information Technology and Computer Science, 2018)
This research was conducted to study data mining using K-Means algorithm which is implemented in the selection of potential customers in MC Laundry. data collected through observation and interviews conducted to the owner of the company concerned. Further data is analyzed to determine the data needed in the process of determining potential customers. From experiments conducted using K-Means algorithm and using Tanagra Software can provide accurate results in classifying potential customers. Keywords: Data Mining, K-Means Algorithm, Tanagra Software